Jordanian migration and mobility in the Middle Bronze Age (ca. 2100–1550 BCE) at Pella. (22nd November 2021) - Stantis, Chris; Maaranen, Nina; Kharobi, Arwa; Nowell, Geoff M.; Macpherson, Colin; Schutkowski, Holger; Bourke, Stephen
Abstract: The site of Pella, located in the foothills of the east Jordan valley, was a prosperous city–state throughout the Middle Bronze Age (MBA, ca. 2000–1500 BCE). As part of a widespread trading network, Pella enjoyed extensive socio‐economic relationships with Egypt, Cyprus, and the Aegean, Anatolia, and Babylonia during this period. We report isotopic analysis ( 87 Sr/ 86 Sr, δ 18 O, and δ 13 C) from enamel of 22 human permanent second molars of which 13 second lower molars were used for an additional biodistance analysis based on ASUDAS. The multidisciplinary approach investigates the ancestral background of MBA Pella and the degree of temporary or more permanent relocation from other settlements. Ancillary to carbonate isotope analysis for migration investigation, dietary information in the form of δ 13 Ccarbonate was also collected. δ 13 Ccarbonate values (mean −12.3‰ ± 0.4 SD) suggest a uniform diet reliant on C3 cereals and legumes as crops and animal fodder, adhering to expected Bronze Age Levantine dietary norms. Two methods are used to identify non‐locals. Using a biospheric baseline, three individuals with non‐local 87 Sr/ 86 Sr ratios are identified. Bagplot analysis of both 87 Sr/ 86 Sr and δ 18 O data suggests that three individuals (14%) grew up elsewhere; two individuals who were already identified as 87 Sr/ 86 Sr outliers using biospheric data and one more with outlying δ 18 O values. All individuals identified as non‐locals, using either method, are from one tomb, Tomb 62. The dental nonmetric traits indicated diverse morphology and subsequent ancestry for Tomb 62 (11/13), whereas primary burials (2/13) clustered together. The commingled condition of Tomb 62 material prevented a more exhaustive biodistance analysis, but the tentative results coincide with interpretations of the tomb. Significant movements of populations throughout the Middle Bronze Age are evidenced through funerary rituals and architecture, and this study demonstrates that Pella, thought to be peripheral, nonetheless had some permanent movement evidenced through isotopes and ancestry analysis.